(untitled) (Proceedings of the YSU B: Chemical and Biological Sciences, 2021)
Morphofunctional changes in the lungs of rats under the influence of aflatoxin B1 were studied. The data obtained indicate that aflatoxicosis causes marked regressive changes due to pulmonary insufficiency, which are accompanied by massive destruction of lung cells, the presence of altered fields of view of emphysema, diffuse inflammatory foci, as well as an increase in the number of mast cells.